Dinámica poblacional de Metamicrocotyla macracantha (Monogenea: Microcotylidae) parásito de Mugil cephalus (Pisces: Mugilidae) en la costa central peruana - Luque, José Luis (Universidad de Costa Rica, 1994)
Infestation by the monogenean Metamicrocotyla macracantha was studied from 1983 to 1986 in 584 fishes (Mugil céphalits) from the central Peruvian coast. Prevalence, abundance and mean intensity of infestation were- 60.8%, 2.14 and 3.53, respectively. A total of 1 252 parasites were collected; they had an overdispersed distribution and a low degree of aggregation. Longer fishes were more heavi1y infested, but sexes did not differ. The infestation . showed no significant seasonal variations. The parasite preferred the first branchial pairo Because of an absence of drastic temperature changes, the central Peruvian coast is a favorable environment for the continuity of the tife cycle of M. macracantha